Effectiveness of incentive spirometry in patients following thoracotomy and lung resection including those at high risk for developing pulmonary complications - 580242 Agostini, Paula author; Naidu, Babu author; Ceislik, Hayley author; Steyn, Richard author; Rajesh, Pala Babu author; Bishay, Ehab author; Kalkat, Maninder Singh author; Singh, Sally author (2013)
PSZJBL